REPOSISI FILSAFAT ISLAM SEBAGAI BASIS PENGEMBANGAN ILMU INTEGRALISTIK - Muhammad Zainal Abidin (UIN Antasari Banjarmasin, 2015)
The construction of integrative science is one of the main discourses in the Islamic scholarly discourse today. There is a great hope that the Islamic scientific products not only based on Islamic values, but also relevant to the needs of Muslims today. This paper intends to reposition the Islamic philosophy as a basis for the development of integrative science. There are three issues inIslamic philosophy, namely the question of divinity (Ilahiyyah), the issue of nature (kauniyyah), and humanitarian issues (insâniyyah) called metaphysics trilogy. The third issue, namely God, Nature, and Man will bear fruit to the beliefs about the ontological status of each part of the object which then became the development of integrative science. The ontology study will affect to the epistemological aspects, particularly with regard to the sources of knowledge. There are three sources that are required to be explored in depth by Muslims, which is associated with signs to the glory of God in the form of the verses of qauliyyah, the verses of kauniyyah, and the verses of humanity. Exploration on the three verses will produce knowledge, which all have a strong spiritual sense that it is all aimed to understand the greatness of God. As for the axiological sphere will produce a pattern of a harmonious relationship and intact in the form of hablum minallâh, hablum minalkawn , and hablum minannâs . The third pattern is the description of the relation of this relationship should be built by a Muslim, in his position as Khalifatullah and at the same time as 'Abdullah.